2007
DOI: 10.1097/jom.0b013e31802f09ee
|View full text |Cite
|
Sign up to set email alerts
|

Do Long Workhours Impact Health, Safety, and Productivity at a Heavy Manufacturer?

Abstract: Much previous work has suggested that long workhours generate a wide range of adverse outcomes across the employee continuum. This study found no evidence for pervasive workhour effects. Rather, long workhours--especially weekly schedules at the 60 hour or above mark--can lead to problems in certain areas of health and safety. More research is needed that tests group differences across segmented characteristics (eg, poor versus good health) but keeps workhour impact in perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 19 publications
1
35
1
Order By: Relevance
“…Most earlier studies reported an increased risk of depression or poor mental health in relation to working long hours regardless of statistical significance (10-16, 19, 22, 24), while a few studies are consistent with findings of the present study (9,13,18). Two studies reported no association (17,20).…”
Section: Earlier Studiessupporting
confidence: 82%
See 2 more Smart Citations
“…Most earlier studies reported an increased risk of depression or poor mental health in relation to working long hours regardless of statistical significance (10-16, 19, 22, 24), while a few studies are consistent with findings of the present study (9,13,18). Two studies reported no association (17,20).…”
Section: Earlier Studiessupporting
confidence: 82%
“…Earlier studies have implied a potential relationship between long work hours and depression (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), but several limitations preclude causal inference: (i) the application of a cross sectional study design in the majority of the studies (11)(12)(13)(14)(15)(16)(17) disguises the direction of association between long work hours and depression; (ii) the low response rates, ranging from 35-58%, (9-13, 15, 18, 19) increase the risk of selection bias; (iii) self-reporting of exposure (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and outcome (9)(10)(11)(12)(13)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also excluded studies with overlapping data with selected studies (33)(34)(35)(36)(37)(38)(39)(40), those without adjustment for baseline mental health (41)(42)(43), and those prospective studies in which exposure and outcome were temporally overlapping (44,45). However, we performed a descriptive, qualitative analysis of studies which included prospective analysis with continuous outcomes rather than outcomes indicating onset of illness (46,47), a study with exposure treated as a continuous variable (48), longitudinal within-subject design with continuous outcomes (49), and broader mental health outcomes, such as antidepressant use (50, 51), all treated mental disorders (52), or disability claims due to all mental disorders (53). Results of these studies are presented in supplementary table B, www.sjweh.fi/show_abstract.php?abstract_id=3712.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The study concluded that fatigued employees cost U.S. employers $136.4 billion per year in health-related LPT-$101 billion more than workers without fatigue. The impact of long hours of work and fatigue on health related problems and injuries ranging from minor workplace incidents to severe accidents has been studied in detail by Allen et al [3]. Fatigue induced accidents are also not new or never heard of.…”
Section: Introductionmentioning
confidence: 99%